The Influence of Health Promotion Interventions Counseling and Peer Education Groups on Clean and Healthy Living Behaviors of Students in Islamic Boarding Schools - Sari, Puspita; M. Ridwan; Silvia Marwati Perdana (Jurnal Promkes: The Indonesian Journal of Health Promotion and Health Education, 2024)
Background: The concept of healthy students is related to clean and healthy living behavior (PHBS) in the Islamic boarding school environment, which combines clean and healthy living behavior (PHBS) in educational institutions and the home environment. Aims: To determine the effect of counseling and peer education groups on the clean and healthy living behavior of students at the Irsyadul Ibad Islamic boarding school. Method: This research is an experimental study using a factorial design with two variables, counseling and peer education. The research sample was 84 students divided into 4 different groups, namely the combination group (counseling and peer education), the counseling group, the peer education group, and the control group. Each group lives in a different dormitory. The health promotion intervention was carried out for 15 days with 10 meetings to discuss clean and healthy living behavior. The statistical tests used were paired t-test and Wilcoxon to determine the differences in values before and after treatment. Kruskall Wallis and Mann Whitney were used to determine the differences in the scores of each group. Results: There are significant differences in knowledge and attitude values before and after treatment, namely: combination group (counseling and peer education), Knowledge p= 0.003, attitude p= 0.009, Knowledge counseling group p= 0.001, attitude p= 0.030 peer group education knowledge p= 0.000, attitude p= 0.001 and control group knowledge p= 0.067, attitude p= 0.053. There are differences in knowledge and attitudes in each group, namely the combination group (counseling and peer education), with the control group, knowledge p = 0.000, attitude = 0.000, counseling group with the control group, knowledge p = 0.000, attitude p = 0.000 peer education group with the control group knowledge p=0.000 attitude p= 0.000. Combination group (counseling and peer education), with knowledge counseling group p=0.063 attitude p= 0.134 combination group (counseling and peer education), with peer education knowledge p=0.079, attitude p=0.095. Counseling group with peer education group knowledge p= 0.332, attitude p=0.424. Conclusion: Combination groups (counseling and peer education), counseling groups, and peer education groups influence clean and healthy living behavior among students at the Irsyadul Ibad Islamic Boarding School.